DESIGN TABLE BOARD GAME FOR SOCIAL INTERACTION IN THE BLIND, CASE STUDY YPAB SLB TEGALSARI SURABAY - Choirul Anam; Muria Ilham Priharto (Ide dan Dialog Desain Indonesia (Idealog), 2021)
This study aims to overcome the bad social-emotional problems of children as well as to invite blind children to participate in playing and not forget to prioritize a special design aesthetic for blind children. The research results found are the results of primary data collection from observations of daily activities of the subject as well as interviews with the subject, teacher, and subject's parents and secondary data obtained from literacy results from related research sources. Research subjects were taken from students of SLB YPAB TEGALSARI SURABAYA. The research method used is to examine primary data and secondary data so that in finding these products it is found from the combined results of the analysis of the behavior patterns of blind children with design analysis, namely material / material, shape, color, and system. In the final result, a traditional game innovation is found that is inspired by a chess board that is often played in schools and modified into a snake and ladder board game for the blind. Keywords: Design, Board game, Snakes and Ladders, Blind